1996
DOI: 10.1103/physrevb.53.10852
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growth direction and strain conditions on the band lineup at GaSb/InSb and InAs/InSb interfaces

Abstract: strain is shown to strongly affect the VBO; in particular, as the pseudomorphic growth conditions are varied, the bulk contribution to the band line-up 1 changes markedly, whereas the interface term is almost constant. On the whole, our calculations yield a band line-up that decreases linearly as the substrate lattice constant is increased, showing its high tunability as a function of different pseudomorphic growth conditions. Finally, the band line-up at the lattice matched InAs/GaSb interface determined usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Note that the value (0.17 eV) obtained in Ref. 5 for InAs/Insb [111] grown on an average substrate is in good agreement with the one derived from Fig. 3 (a) (0.19 eV).…”
Section: Valence Band Offsetsupporting
confidence: 87%
See 1 more Smart Citation
“…Note that the value (0.17 eV) obtained in Ref. 5 for InAs/Insb [111] grown on an average substrate is in good agreement with the one derived from Fig. 3 (a) (0.19 eV).…”
Section: Valence Band Offsetsupporting
confidence: 87%
“…are equal to those used in a previous study and reported elsewhere. 5,17 In order to check the convergence of the valence band offset as a function of the cell dimension, we also performed calculations for (GaSb) 4 /(InSb) 4 and (InAs) 4 /(InSb) 4 SLs grown on the same substrates.…”
Section: Structural and Technical Detailsmentioning
confidence: 99%
“…This valence band offset corresponds to an unstrained offset for the lnAs/lnSb binaries of 0.36 ±0.04 eV, with the valence band of InSb being higher in energy [6]. Recent first-principles local-density-function calculations predict an unstrained lnAs/lnSb valence band offset of 0.50 eV, in reasonable agreement with our experimental value [12,34]. Cyclotron resonance provided independent confirmation of the type II band offset with observation of the low in-plane effective mass, hole ground state in a p-type InASo.lsSbo.8slInSb SLS [33].…”
Section: Sb-rich Inassb Superlattices and Long Wavelength Infrared Dsupporting
confidence: 86%
“…Models which explain the energy of InAsSblInAs heterostructures with large type II band offsets [45] or inverted band offsets [46] are inconsistent with both our optical studies [15,18] and consensus theoretical predictions [12,34]. Quantum size studies have shown that the electrons are confined in the InAsSb layer of MOCVD-grown lnAsSblInAs and lnAsSblInGaAs heterostuctures [15,16,18].…”
Section: As-rich Inassb Superlattices and Mid-wave Infrared Lasers Amentioning
confidence: 55%
See 1 more Smart Citation